A case study on the management practices used by Chinese-Filipino entrepreneurs of selected small, medium and large scale garment manufacturing companies - Ki, Jennifer Cua
This study aims to have a batter understanding of Chinese management practices in the garment industry. The problem of the study is, "What are the practices, beliefs and traits of the Chinese-Filipino which influence the management of their garment manufacturing company?"The study focused on the production and personnel management practices used in three selected Chinese-Filipino garment-manufacturing companies. Topics discussed under the production management include: the organizational structure of the company, design, inventory control practices, quality control practices and plant maintenance practices. Personnel management practices cover communication with employees and training of personnel. This thesis seeks to identify the distinct Chinese-Filipino practices used in the above topics, and to learn the particular beliefs, traits and values, which influence them. It is hoped that this study will add more knowledge and understanding about the Chinese-Filipino ways of managing a garment manufacturing company in three different levels of establishment. This research is in-depth case studies of three different levels of garment subcontracting companies. It is also a comparative analysis of the three levels of business. It aims to make a comparative analysis of three garment manufacturing companies - small, medium and large-scale enterprises which make up the purposive sample of this study. The case studies of these enterprises are based on the responses of key officers to unstructured questionnaires and through structured observation. The structured observation used the same areas covered in the interview guide for its outline. An unstructured interview method was used to allow the researcher to be flexible in gathering necessary information. It allows more meaningful data collection and greater depth. The research showed that there are distinct practices in the garment manufacturing industry, influenced by beliefs, traits and values that are clearly "Chinese." These include such influences as the Confucian philosophy, frugality, the importance of trust, belief about colors, and their ideal of beauty. Their management practices are also influenced by their particular situation in the Philippines, where the gap between the rich and the poor is very marginal. They do not want to make any unnecessary show of wealth, thereby causing the resentment of the majority of the population.